Survey of topical exposure concerns for patients and caregivers dealing with atopic dermatitis - Ratley, Grace; Sun, Ashleigh A.; Capozza, Korey; Barta, Kelly; Myles, Ian A. (Frontiers in Allergy, 2023)
Background Despite the recent expansion of treatment options in atopic dermatitis (AD), most management responsibilities fall on the patient and/or caregivers. Disease control often requires vigilance about and avoidance of common exposures, however the concerns for patients and caregivers living with AD have not been well enumerated. Methods An IRB approved survey was distributed to the public to evaluate the patient and caregiver concerns for topical exposures and potential triggers. Results 323 people accessed the link to the survey with 259 providing response to at least one section of questions (response rate 80.2%). Results indicated that temperature and other weather related changes were the most common trigger. Nearly all respondents avoided at least one topical ingredient, with fragrances being the most common. Steroid exposure was common, however respondents expressed concerns about overall steroid exposure. Conclusions Our results attempt to enumerate the daily topical exposure concerns for patients and caregivers living with AD. While our online survey is both limited and without mechanistic insights, our results provide insight to providers by highlighting the role of temperature in AD symptoms; identifying commonly perceived triggers; indicating the value of provider insight for topical product selection; and indicating that no specific aspect of topical corticosteroid exposure may alleviate the general steroid concerns for patients or caregivers.